Non-adopters of Social Media: Comparing their Lifestyles, Perceived Innovation Attributes, and Sociodemographic Attributes with All-adopters, Partial-adopters, and Minimum-adopters - Shu-Chu Sarrina Li; Yen-Shen Chen (International Telecommunications Society (ITS), 2017)
This study adopted Rogers' diffusion of innovation model to investigate the adoption of three social media with high penetration in Taiwan—Facebook, Line, and email. Special attention was paid to identifying the factors that differentiated the non-adopters (who did not adopt any of the three social media) from the all-adopters (who adopted all three social media), the partial-adopters (who adopted two social media), and the minimum-adopters (who adopted only one social medium). Two methods were adopted; one was to conduct 20 intensive interviews and the other was to administer a nationwide telephone survey with 1042 valid questionnaires. Two conclusions were obtained: (1) The characteristics of the non-adopters were congruent with those of the laggards in Rogers' model, demonstrating that the non-adopters were less educated, less affluent, older, and used mass media less frequently than the other types of adopters; (2) the lifestyles of the non-adopters differed greatly from those of all-adopters, partial-adopters, and minimum-adopters.
Keywords: 330; Facebook; Line; email; Rogers' diffusion of innovation model; non-adopters; lifestyle